(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
In this article the final proof of the equivalence of polynomial (P) and non-polynomial classes (NP) are provided within the given Klaus Schneider’s regular expression forms which tend to be exponential in size and the problem in overall is seen to be in EXPTIME and EXPSPACE and, thus, NP-complete. We provide the full history of this proof with the experimentally obtained results. Our application of the obtained singular algorithm in terms of computational complexity responds to the famous theorem like “P versus NP” which wasn’t solved before and now is resolved in this work. We will also discuss the future of the question from past as the novel proof is given.